Controllable synthesis of uniform MgAl‐hydrotalcite nanoplates and their size‐dependent on anti‐corrosion properties of carbon steel. (26th October 2022) - Vuong, Phan Minh; Thoa, Tran Thi Kim; Nhu, Pham Quynh; No, Nguyen Thi Hong; Ty, Nguyen Minh; Huy, Do Manh; Thao, Phan Thanh; Hang, To Thi Xuan
Abstract: Hydrotalcite, a three dimensional anionic clay with a high anion exchange capacity, is a potential candidate for application in various fields, especially in anti‐corrosion. This study reports a facile synthesis to control the uniform particle size and well‐defined MgAl‐hydrotalcite hexagonal nanoplates in stable homogeneous suspension. The synthesized crystals were characterized by XRD, FTIR, TG‐DSC, ICP‐MS, and FE‐SEM. The results show that the crystals are well‐controlled particle size and morphology of individual sheets. The stability of products was confirmed using zeta potential measurement for three months at room temperature, and the lateral dimension was controlled between 50 and 300 nm. The influence of particle size on the corrosion inhibition effect of carbon steel was investigated by electrochemical measurement. The polarization curves and impedance diagrams indicated that the corrosion resistance effect of MgAl‐HT depends on both sides of the surface electric and the level deposition of crystallite on the electrode surface. The highest effective inhibition is 80.18 %, archiving on the diameter across 152.1 nm of hexagonal nanoplates. Abstract :